2017
DOI: 10.1590/1983-80422017251169
|View full text |Cite
|
Sign up to set email alerts
|

Uso da casuística no processo ensino-aprendizagem de bioética em saúde

Abstract: There are several bioethical models capable of contributing to decision making in health. The casuistic model works with the analysis of real cases for decision making regarding bioethical problems. It is conducted with 16 academic scholars from the health field with the objective of identifying academic experiences in the teaching-learning process of bioethics. It uses the case method, based on the casuistic model. It is a descriptive, qualitative study using thematic analysis, where two categories emerged: "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
3
0
3
Order By: Relevance
“…A maior parte dos artigos desta revisão integrativa abordou, analisou ou comparou a aplicação de estudos de caso no ensino de Ética, Bioética e Deontologia. Historicamente, o paradigma casuístico emerge no século 16 e 17 como uma resposta aos problemas morais do mundo moderno e suas transições, analisando circunstâncias concretas e propondo soluções comparativas com casos já vivenciados [41][42][43] , seguindo os paradigmas da Aprendizagem Baseada em Problemas e Metodologia da Problematização, que serão apresentados e discutidos mais adiante 40,44 .…”
Section: Uso Da Casuísticaunclassified
“…A maior parte dos artigos desta revisão integrativa abordou, analisou ou comparou a aplicação de estudos de caso no ensino de Ética, Bioética e Deontologia. Historicamente, o paradigma casuístico emerge no século 16 e 17 como uma resposta aos problemas morais do mundo moderno e suas transições, analisando circunstâncias concretas e propondo soluções comparativas com casos já vivenciados [41][42][43] , seguindo os paradigmas da Aprendizagem Baseada em Problemas e Metodologia da Problematização, que serão apresentados e discutidos mais adiante 40,44 .…”
Section: Uso Da Casuísticaunclassified
“…However, this research revealed low overall performance of G1, which, when added to the cases of superior performance of G2, shows that the instruction of students, even among those who attended at least one of the two disciplines that address medical ethics, is insufficient to deal with other dilemmas. To reverse this situation, medical ethics should be addressed in more than one moment in graduation, facilitating the clinical application of the concepts learned 1,2,[30][31][32]39 . The university where this research was conducted seeks to correct this flaw with the inclusion of the academic discipline Medical Ethics and Communication Skills.…”
Section: Dilemmas Section In Clinical Casesmentioning
confidence: 99%
“…It is necessary, in addition to longer time of contact with the theme, that diversified methods be used in the learning process. There are several nontraditional teaching resources that can be applied in this case, such as movies, dilemma scenarios, casuistry, stagings, theatre plays, simulations, video conferences, seminars, lectures, workshops and case discussions 1,3,5,[29][30][31][32]34,38,39,41 .…”
Section: Dilemmas Section In Clinical Casesmentioning
confidence: 99%
“…Outro fator a ser considerado é o Código de Ética Odontológico, que embora tenha sido reformulado há pouco tempo, ainda é focado em questões legais e não em conflitos éticos, centrado no paciente(NÓBREGA et al 2015). Cabe ao docente inclui-la no processo de ensino-aprendizagem tanto no currículo formal, como no oculto (FINKLER; CAETANO; RAMOS, 2014), motivando as decisões pautadas nos valores, usando metodologias problematizando casos reais(LEITE et al 2017).…”
unclassified